Influence of temperature and humidity on the stability of medicines in dosage administration aids - Jiumjaiswanglerg, Siriwimol (Curtin University, 2008)
The purpose of this study was to evaluate the chemical stability of six medications in two types of unit-dose packaging, one was Webster-Package and another was a plastic seal unit-dose package. Stability was observed in terms of the drugs’ active ingredients and appearance of tablets and/or capsules. The study was commenced under condition of 35 ºC and 90% RH that related to temperature and humidity of tropical climate areas. A period of sixty days was chosen as the time period since unit-dose packages have to be delivered to patients and patients have to use the medications for up to one month. Six medications tested in this study were aspirin tablets 100mg (DBL Aspirin®), atorvastatin 40mg (Lipitor®), gliclazide 30mg MR (Diamicron MR®, and Oziclide®), metformin (GenRx Metformin® 500mg, and Formet® 1000mg), omeprazole 20mg (Omeprazole Winthrop®, and Omepral®), and ramipril 10mg (Ramipril Winthrop®, Ramipril Sandoz®).Each medication was transferred from an original package into eighteen different wells of small size Webster-Package. All six medications were also packed together into an other eighteen different wells of large size Webster-Package. To test the stability of the medicines in the Webster-Package, all of the packs were stored at 35 °C and 90% humidity for 60 days. Ramipril and omeprazole were also examined in another test condition (30°C and 90% RH) for 28 days. In addition, unit-dose packages from the Northern Territory of South Australia were tested. Medications were packed into clear sealed plastic bags by Stuart Park Pharmacy and tested using the same control condition. Time points for analysis were undertaken at day 0, 7, 14, 21, 28, and 60. Three samples were collected and triplicate tests were done for each sample. Shape and colour of the tablets were evaluated. Quantitative results were gained by using High Performance Liquid Chromatography (HPLC). Results of the stability testing at each time point were compared with their standard curves. Visual stability alterations were found in aspirin tablets (DBL Aspirin®), omeprazole tablets (Omeprazole Winthrop®, and Omepral®), and ramipril capsules (Ramipril Winthrop®, Ramipril Sandoz®) in both groups of Webster-Packages and unit-dose packages. Fading of ramipril capsules’ colour and sealing of cap and body of the capsules were found in both test conditions. Film-coatings of omeprazole tablets were cracked in both test conditions. Chemical stability alterations were found in omeprazole tablets used in unit-dose package. The results showed that in both experimental conditions omeprazole active ingredient was detected at levels of less than 90% of the active ingredient in the control tablets at Day 14 of the experiment.It may be concluded that not all of these medications can be repackaged into Webster-Packaging and unit-dose packaging. Pharmacists should be concerned about chemical properties of drugs, especially hydrolysis, photosensitivity, and heat resistance properties, before deciding to repackage them.